Kinematic analysis of the block start and 20-metre acceleration phase in two highly-trained sprinters: A case report - Janowski, M.; Zielinski, J.; Wlodarczyk, M.; Kusy, K. (Baltic Journal of Health and Physical Activity, 2017)
Background: The main purpose was to evaluate individual kinematic characteristics in highly trained sprinters during the "set" position, block clearance and a 20-m acceleration phase, as well as to determine differences and/or technique similarities. Material/Methods: The measurements were carried out on two sprinters, members of the Polish national team. A wireless portable MyoMotion system (Noraxon Inc., USA) was applied. Angular changes and accelerations of all limbs, trunk and head were measured. Results: Increased motion asymmetry between sides brought about stride fluctuation and worsened sprint performance. This effect occurred when the sum of the discrepancies for hip, knee and ankle joints exceeded 20° or if one joint exceeded 10°. For acceleration, the adverse effect occurred when the range exceeded 1.40 G during the acceleration phase. Greater asymmetry resulted in lower acceleration during block clearance. During block clearance rear hip and right knee angles did not exceed 110º and 100°, respectively, in the best attempts. The "set" position seemed to have little impact on performance. Conclusions: Sprinters exhibit individual kinematic characteristics. Fast block clearance and stride symmetry are key factors affecting sprint performance during the 20-metres acceleration phase. Additional research is necessary to determine the most effective pattern.